Methylphenidate Treatment and Risk of Psychotic Disorder - Healy, Colm; O’Hare, Kirstie; Lång, Ulla; Metsälä, Johanna; Pulakka, Anna; McGrath, Jane; Migone, Maria; Keating, Dolores; Romaniuk, Liana; Gyllenberg, David; Kajantie, Eero; Perrett, George; et al. (American Medical Association (AMA), 2026)
Importance  Methylphenidate is the leading pharmacological treatment for attention-deficit/hyperactivity disorder (ADHD) in childhood and adolescence. Individuals with ADHD have a higher risk of psychosis, but the long-term relationship between methylphenidate and risk of developing psychotic disorders is unknown.
Objective  To estimate the relationship between methylphenidate treatment and the risk of nonaffective psychosis in children and adolescents diagnosed with ADHD.
Design, Setting, and Participants  This cohort study included instrumental variable analysis of data linkage from multiple national Finnish registries for all individuals born from 1987 to 1997 (n = 697 289). These registries were used to identify childhood and adolescent ADHD diagnoses (age <18 years) from 2003 onwards. Data were analyzed from June 2023 to December 2025.
Exposure  Cumulative amount of treatment with methylphenidate used in 4 intervention windows: within 1, 2, 3, and 4 years after ADHD diagnosis. Hospital district prescribing propensities (average prescribing within each hospital district, within each intervention window) were used as instruments.
Main Outcome and Measures  Diagnosis of nonaffective psychotic disorder (by code from International Statistical Classification of Diseases and Related Health Problems, Tenth Revision) by the end of follow-up (December 31, 2016). Instrumental variable analyses were conducted using 2-stage least squares modeling and the Anderson-Rubin test. Risk differences (RDs) were estimated for each intervention window.
Results  Among 3956 individuals diagnosed with ADHD (3181 male [80.4%], 775 female [19.6%]; median [IQR] age, 14.16 [11.78-15.93] years), 2728 (69.0%) received methylphenidate at least once. A total of 222 individuals (5.7%) were diagnosed with nonaffective psychosis by mean (SD) age 22.16 (2.39) years (range, 19.00-29.81 years). There was substantial variation in hospital district prescribing propensity (for example, first-year range, 0.07 to 0.30). Instrumental variable analysis indicated that sustained treatment with methylphenidate (30 mg/d) was not associated with the risk of nonaffective psychosis in the overall ADHD sample (1-year RD, −0.14; 95% CI, −0.85 to 0.42; and 4-year RD, −0.15; 95% CI, −0.49 to 0.11). Secondary analyses indicated a reduced risk of nonaffective psychosis among individuals diagnosed in childhood (age <13 years: 3-year RD, –0.24; 95% CI, –0.45 to –0.03; P = .03; 4-year RD, –0.21; 95% CI, –0.48 to –0.07; P = .02). An insufficiently strong instrument precluded the same secondary analyses in those diagnosed in adolescence.
Conclusion and Relevance  This study of national Finnish registry data for individuals with ADHD found no overall relationship between sustained treatment with methylphenidate risk of nonaffective psychosis; in secondary analyses, a potentially protective effect of methylphenidate treatment against later psychosis in children diagnosed with ADHD was found. Further research is needed to evaluate potential effects of treatment in individuals diagnosed in adolescence and adulthood.